International Criminal Law and New Zealand Refugee Status Determinations: A Case Note on Attorney-General v Tamil X - Watt, Ella (Victoria University of Wellington Law Review, 2012)
This article considers Attorney-General v Tamil X, a recent New Zealand Supreme Court decision on refugee status determinations. Specifically, it considers the approach taken to art 1F of the Refugee Convention in decisions on the exclusion of claimants from refugee status. As claims are increasingly affected by art 1F considerations, it is imperative that the law in this complicated area is clear and just. This article traces Tamil X's advancement through the courts, and presents an analysis of the Supreme Court's judgment. The article also recommends some future developments for the jurisprudence on the exclusion clauses, specifically the adoption of a modified version of the ICTY jurisprudence on joint criminal enterprise.